Genetic patterns reveal northward range expansion and cryptic diversity in Nalbant's spined loach, Cobitis nalbanti sensu lato (Teleostei: Cypriniformes: Cobitidae). Issue 1 (2nd January 2020) - Jeon, Yeon Seon; Ko, Myeong-Hun; Vasil'eva, Ekaterina D.; Myung, Ra-Yeon; Won, Yong-Jin
Abstract : The morphologically similar populations of the Korean freshwater spined loach recently described as a new species Cobitis nalbanti (Actinopterygii: Cypriniformes: Cobitidae) inhabit the rivers and streams on the Korean Peninsula that flow into the Yellow Sea and the Korea Strait. These shallow sea areas have experienced recurrent sea-level rises and falls. In this study, we investigate the impact of repeated disconnection and reconnection of rivers on the population genetics and morphological variation of C. nalbanti . A total of 264 individuals of C. nalbanti were collected from 17 localities covering the entire distribution range of this species in South Korea. We examined multi-locus genetic data including a mitochondrial gene, seven nuclear genes and eight microsatellite loci, and scrutinized 31 morphological variables based on 26 morphometric and 3 meristic characters. We uncovered a population genetic structure and noticeable morphological variation among populations approximately corresponding to the geography of river basins along the Yellow Sea. Overall genetic diversity was significantly reduced in the more northern populations, suggesting range expansion from ancestral southern populations into northern rivers via the paleo-Yellow River system in the Yellow Sea during glacial periods of lowered sea levels. A northward range expansion hypothesis was strongly supported by the reconstruction of geographic ranges of ancestral species and/or populations based on phylogenetic analyses. Both mitochondrial and nuclear phylogenetic trees revealed a relatively highly divergent lineage of C. nalbanti in the southernmost populations (Tamjin lineage). Noticeable differences in morphological variables between the Tamjin lineage and other lineages of C. nalbanti also suggest potential separate specific status of the former. The close phylogenetic relationships between the Tamjin lineage and the Japanese species of Cobitis signify interaction or exchange between the Korean and Japanese cobitids and imply that there was historically at least one freshwater passage on the terrestrial bridge between the Korean Peninsula and the southwestern part of the Japanese archipelago.